Low-dose dose-response for reduced cell viability after exposure of human keratinocyte (HEK001) cells to arsenite. (2017) - Bogen, Kenneth T.; Arnold, Lora L.; Chowdhury, Aparajita; Pennington, Karen L.; Cohen, Samuel M.
Abstract: The in vitro arsenite (As III ) cytotoxicity dose-response (DR) of human keratinocytes (HEK001) was examined at greater statistical resolution than ever previously reported using the MTT assay to determine cell viability. Fifty-four 96-well plates were treated with As III concentrations of 0.25, 0.5, 1, 2, 3, 4, 5, 7, 10, 15, 20, 25, or 30 μM. Because of unexpected variation in viability response patterns, a two-stage DR analysis was used in which data on plate-specific viability (%), estimated as 100% times the ratio of measured viability in exposed to unexposed cells, were fit initially to a generalized lognormal response function positing that HEK001 cells studied consisted of: a proportion P of relatively highly sensitive (HS) cells, a proportion P o of relatively resistant cells, and a remaining (1– P – P o ) fraction of typical-sensitivity (TS) cells exhibiting the intermediate level of As III sensitivity characteristic of most cells in each assay. The estimated fractions P and P o were used to adjust data from all 54 plates (and from the 28 plates yielding the best fits) to reflect the condition that P  =  P o  = 0 to provide detailed DR analysis specifically for TS cells. Four DR models fit to the combined adjusted data were each very predictive (R 2  > 0.97) overall but were inconsistent with at least one of the data set examined (p < 10 −5 ). Adjusted mean responses at ≤3 μM were approximately equal (p > 0.30) and exceeded 100% significance (p ≤ 10 −6 ). A low-dose hormetic model provided the best fit to the combined adjusted data for TS cells (R 2  = 0.995). Marked variability in estimates of P (the proportion of apparent HS cells) was unexpected, not readily explained, and warrants further study using additional cell lines and assay methods, and in vivo .